2015
DOI: 10.1007/s00234-015-1604-7
|View full text |Cite
|
Sign up to set email alerts
|

Temporal bone and cranial nerve findings in pontine tegmental cap dysplasia

Abstract: Patients with PTCD have highly characteristic temporal bone and cranial nerve findings on both CT and MR. Recognition of these findings is important for improved diagnosis of this rare disorder, particularly by CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…In the largest reported series of 16 patients reviewed retrospectively and published recently in 2016 by Nixon et al ., the authors found associated duplication of one or both internal auditory canals in all but one patient. [ 8 ] Associated cochlear nerve aplasia and either atresia or stenosis of internal auditory canals was also observed in their study. However, our patient did not reveal any temporal bone and cochlear nerve abnormality.…”
Section: Discussionsupporting
confidence: 52%
“…In the largest reported series of 16 patients reviewed retrospectively and published recently in 2016 by Nixon et al ., the authors found associated duplication of one or both internal auditory canals in all but one patient. [ 8 ] Associated cochlear nerve aplasia and either atresia or stenosis of internal auditory canals was also observed in their study. However, our patient did not reveal any temporal bone and cochlear nerve abnormality.…”
Section: Discussionsupporting
confidence: 52%
“…PTCD is a brainstem malformation ( 1 , 3 , 4 ) , initially described in 2007 by Barth et al ( 5 ) ; to date, fewer than 50 cases have been reported ( 4 ) . The main signs and symptoms are auditory deficiency, in 92% of cases; cognitive deficit, in 76%; deglutition disorders, in 64%; facial paralysis, in 60%; abnormal eye movement, in 60%; trigeminal paresthesia, in 60%; ataxia, in 56%; hypotonia; cyclic vomiting syndrome; and various neurological disorders of the third to the eighth cranial nerves ( 4 , 6 , 7 ) .…”
mentioning
confidence: 99%
“…PTCD is a brainstem malformation ( 1 , 3 , 4 ) , initially described in 2007 by Barth et al ( 5 ) ; to date, fewer than 50 cases have been reported ( 4 ) . The main signs and symptoms are auditory deficiency, in 92% of cases; cognitive deficit, in 76%; deglutition disorders, in 64%; facial paralysis, in 60%; abnormal eye movement, in 60%; trigeminal paresthesia, in 60%; ataxia, in 56%; hypotonia; cyclic vomiting syndrome; and various neurological disorders of the third to the eighth cranial nerves ( 4 , 6 , 7 ) . Other potential characteristics of PTCD include hypoplasia of the pons (notably in its ventral aspect); a mass of ectopic dorsal pontine fibers protruding into the fourth ventricle; hypoplasia/agenesis of the middle and inferior cerebellar peduncles; elongation of the superior cerebellar peduncles; cerebellar vermis hypoplasia/ agenesis; absence or malformation of the inferior olivary nuclei; hypogenesis/absence of the third to eighth cranial nerves; costovertebral deformities; and cardiovascular anomalies ( 1 , 3 - 8 ) .…”
mentioning
confidence: 99%
See 2 more Smart Citations